Gene cloning for the isolation of enzymes of membrane lipid synthesis: phosphatidylserine synthase overproduction in Escherichia coli. - Raetz, C R (1977)
We have screened a bank of 2000 E. coli strains carrying hybrid ColE1 plasmids [Clarke, L. & Carbon, J. (1976) Cell 9, 91-99] for those that correct the temperature sensitivity of a mutant in CDP-1,2-diacyl sn-glycerol:L-serine O-phosphatidyltransferase (EC 2.7.8.8, phosphatidylserine synthase). Two hybrid plasmids of this kind (pLC34-44 and pLC34-46) were identified and characterized. Strains carrying these plasmids overproduce the synthase by 6- to 15-fold, as demonstrated by assays of extracts and purification to homogeneity of the overproduced enzyme. The overproduced synthase, like the wild-type enzyme, is found associated predominately with the ribosomal fraction of crude cell extracts. Because the membrane phospholipid composition of these overproducers is not greatly altered, we suggest that the synthase is normally present in excess.